Misconceptions of Intermolecular Forces in General Chemistry Courses - Ulfah*, Maria; Erlina, Erlina; Pratiwiningrum, Firra Meliana; Wafiq, Azwa Fadilla; Juahir, Yusnita Binti (Jurnal IPA & Pembelajaran IPA, 2024)
The misconception is the most topic in chemistry learning that is important to analyze. There are many advantages for lecturers and students to know about misconceptions. This research aims to describe misconceptions in general chemistry courses, especially intermolecular forces (IMFs) topic. The two-tier multiple-choice tests have played an important role in helping researchers determine students level of understanding and in identifying specific misconceptions. The project used a convenience sample of 88 students (76 female and 12 male) chemistry education program that studied IMFs as participants. Misconception knew from the tests second tier, which is the students reason for the answer. Surprisingly, 29 misconceptions were acquired from the test about IMFs concepts. This needs to be a special concern for lecturers of basic chemistry courses in order to evaluate the learning process that has been carried out. Students misconceptions in basic chemistry courses will have an impact on organic chemistry courses because the concept of intermolecular forces will be studied in depth in organic chemistry courses. The success of students in organic chemistry courses is highly dependent on the initial knowledge of students, especially in basic chemistry courses